Inventory, reward value and diversity of Apis mellifera nectariferous and polleniferous forage in Eastern Mau forest, Kenya - Onyango, Philip; Nyunja, Regina; Opande, George; Sikolia, Stephen Fedha (International Journal of Scientific and Research Publications, 2020)
The study was conducted in Eastern Mau is one of the East Mau forest is an important watershed within the Mau Forest Complex, feeding major rivers and streams that make up the hydrological systems of Lake Victoria and inland Lakes of Nakuru, Baringo and Natron to document the bee flora and their respecetive reward value to compliment the participatory forest conservation approaches incorporating the Ogieks who are predominant forest dwellers, and known for bee keeping skills, to aid in bee keeping extension services and by extension forest conservation. Transects were made in three randomly selected strata according to stratified random sampling procedures. The flowering plants were observed for their foraging value based on the Apis mellifera foraging activities using appropriate determination techniques. The study has revealed a total of 86 plant speceis and 36 families foraged by Apis mellifera. Cissus rotundiflora (Vitaceae), Trema orientalis (Ulmaceae), Maerua triphylla (Capparaceae), Aloe secundiflora (Asphodelaceae), Tribulis terrestis (Zygophyllaceae) and Polyscias fulva (Araliaceae) Some of the bee plants are reported for the first time in Eastern Mau. Trees formed 41.86%, Herbs (25.58%), Shrubs (23.25%), and climbers (9.3%) of the bee forage. Fabaceae, Asteraceae, Acanthaceae, Myrtaceae, Euphorbiaceae, and Graminae families contribute the majority of the bee plants in Eastern Mau forest. Index terms: Apis mellifera, bee keeping, bee plants, conservation, Eastern Mau forest
Keywords: Apis mellifera; bee keeping; bee plants; conservation; Eastern Mau forest